2013
DOI: 10.1309/ajcpos9z5kvzsfsc
|View full text |Cite
|
Sign up to set email alerts
|

MS-Based Monitoring of Proteolytic Decay of Synthetic Reporter Peptides for Quality Control of Plasma and Serum Specimens

Abstract: This "proteomics degradation clock" can be used to estimate the preanalytical quality of serum and plasma and might have impact on quality control procedures of biobanking repositories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…1). The time‐dependent decay of intermediate RP‐fragments has been shown in previous work . Here, by reasons of simplified standardization only endpoint measurements after 24 h of incubation time were performed.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…1). The time‐dependent decay of intermediate RP‐fragments has been shown in previous work . Here, by reasons of simplified standardization only endpoint measurements after 24 h of incubation time were performed.…”
Section: Resultsmentioning
confidence: 93%
“…Many substrates of various tumor-associated proteases such as metalloproteases, cathepsins, kallikrein-related peptidases, and the plasminogen activator system have been compiled in databases that offer comprehensive information regarding protease-substrate interactions [18,20]. However, the stability of synthetic peptides in blood specimens is limited due to the high intrinsic proteolytic activity of serum and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…This is also in agreement with findings from. Findeisen et al (25) and Qundos et al (26) In the former study, they found that the concentration of proteolytic fragments changed in a time-dependent manner. And Qundos's investigation found that temperature the samples were kept after collection and time intervals between sample collection and centrifugation can significantly influence the proteins profiles.…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, the analytical monitoring of sample quality is obligatory for improved biomarker discovery and validation studies. Recently we described an external decay marker for quality control monitoring of serum and plasma [7]. However, this approach is restricted to prospective quality control analyses as the synthetic peptide substrate has to be added to serum-and plasma-tubes prior to blood withdrawal and existing collections with native samples are not assessable to this approach.…”
Section: Introductionmentioning
confidence: 99%
“…The cleavage of proteins by endoproteases is generating peptidic fragments that are further trimmed down by exoproteases causing 'ladder like' degradation patterns [10]. This results in the reduction of longer and accumulation of shorter fragments during prolonged incubation [7]. For the selection of appropriate endogenous decay markers we systematically investigated the time dependent changes in peptide profiles of serum specimens that were aged under controlled conditions (1 h to 48 h).…”
Section: Introductionmentioning
confidence: 99%